Reflection on Humanity in Crises: Consumption and World War in Nepali Literature - Phuyal, Komal Prasad (Pragya Darshan प्रज्ञा दर्शन, 2023)
Humanity has undergone multiple crises across time and place along with the evolution of organized human settlement. Generally, human assumptions are supposed to take a rational course of action in society as we carry out various transactions in our quotidian life. However, fissures emerge as errors in human imagination about polity and organized society in the form of wars, leading to larger scale unresolved issues. On the other hand, human beings also face natural microorganisms like bacteria or virus leading to global crises. Humanity has confronted such tension, resulting from such disasters. Such concerns of crises have turned into the subject of contemplation for Nepali literary geniuses in the 1960s. This paper concentrates on two major literary texts from the time: Parijat’s Shirishko Phool (1964) and B. P. Koirala’s Narendra Dai (1970). Textually analyzing the data, this paper examines the mode of reflection on human crises in Nepali literature by analyzing the impacts of consumption as pandemic in Koirala and the World War as the cause of human misery in Parijat. In fact, Koirala’s novella stands as a literary response to pandemic of consumption in his time. This study places Koirala first in the chronology, for his novella, Narendra Dai covers the time span beginning from the end of the World War I (1918) to the great earthquake (1934) in Nepal. Furthermore, Parijat’s Shirishko Phool primarily presents Nepali social world after the World War II. The critical conditions have resulted in miserable state of life at the time. Human beings suffer in both conditions; still, they display high courage and sense of moral integrity to fight against the critical situations in their life.